2004
DOI: 10.1016/j.schres.2004.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of developmental markers in childhood and adolescence and risk for schizophrenic psychoses in adult life. A 34-year follow-up of the Northern Finland 1966 birth cohort

Abstract: SUMMARYChildhood precursors of schizophrenia include multiple abnormalities of development.Continuities between early and subsequent deviance are poorly characterised. We studied associations among premorbid developmental deviance using data at ages 1 year (learning to stand, walk, and speak, attainment of bladder and bowel control) and 16 years (success at school). Generalised linear modelling was used to examine differential linear associations and trends across adult psychiatric diagnoses. In babies who, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 30 publications
2
46
1
1
Order By: Relevance
“…In the context of these normative results and the explanatory model based upon them, how can we interpret our findings in schizophrenia? Compared with the nonpsychotic subjects, people with schizophrenia had significantly delayed motor development in early childhood (persisting at age 16 years [6]), implying abnormally delayed or deviant maturation of motor systems, presumably due to disadvantageous effects of genetic or other early developmental factors. People with schizophrenia were also distinguished by the absence of normative associations between IMD scores and both premotor cortical gray matter volume and fronto-parietal white matter volumes.…”
Section: Discontinuities Between Imd Adult Executive Function and Amentioning
confidence: 98%
See 1 more Smart Citation
“…In the context of these normative results and the explanatory model based upon them, how can we interpret our findings in schizophrenia? Compared with the nonpsychotic subjects, people with schizophrenia had significantly delayed motor development in early childhood (persisting at age 16 years [6]), implying abnormally delayed or deviant maturation of motor systems, presumably due to disadvantageous effects of genetic or other early developmental factors. People with schizophrenia were also distinguished by the absence of normative associations between IMD scores and both premotor cortical gray matter volume and fronto-parietal white matter volumes.…”
Section: Discontinuities Between Imd Adult Executive Function and Amentioning
confidence: 98%
“…Longitudinal epidemiological studies of schizophrenia show early developmental adversity imparting increased risk of adult psychosis, with the emergence of psychotic symptoms preceded by subtle abnormalities of motor coordination (developmental dysmetria), social function, and cognition in childhood and adolescence (4)(5)(6). Typically, cognitive and social malfunction increases during the prodromal period before presentation of the psychotic schizophrenia syndrome, when motor dysfunction indicative of basal ganglia involvement is evident (7).…”
mentioning
confidence: 99%
“…Prospectively collected data from the 1972-73 birth cohort in New Zealand, showed that 20 schizophrenic subjects may have suffered a significant deficit in neuromotor, language, and cognitive development in the first decade of their lives. The compelling evidence linking an array of childhood developmental abnormalities and schizophrenia is echoing with the hypothesis that schizophrenia is a neurodevelopmental disorder, for which causes may be traced to a defect in the early brain development [27][28][29][30] .…”
Section: Analytical Epidemiology: Natural History and Risk Factors Namentioning
confidence: 99%
“…In addition, delay in motor coordination, impaired receptive language and cognitive functions were detectable as early as second year of life. All these early features were independent of socioeconomic, obstetric and maternal factors (6).…”
Section: Hemamali Pereramentioning
confidence: 80%